Análise de associação genômica para resistência à podridão de espiga causada por Fusarium verticillioides - Jong, Guilherme de (2016)
Maize is one of the most cultivated cereals and its extensive cultivation allows a wide range of pathogens to attack the culture. The most important pathogens that attack maize culture are the agents of ear rot, which directly affect grain yield and quality of kernels. Among the main causative agents of ear rot, the rot caused by the fungus Fusarium verticillioides stands out. The identification of causal regions associated with this disease resistance may be a useful tool to improve maize breeding and is also a way to better understand the mechanisms of resistance. In this research, a genome-wide association study was conducted to identify significant associations between markers and possible causal regions related to the resistance of ear rot of corn caused by the fungus F. verticillioides. Two hundred forty-two inbred lines were evaluated in two locations (Lavras and Uberlândia) to the proportion of ears with rot symptoms, i.e., with more than 25% of the ear rotten in relation to the total number of ears. Associations were tested with 23,153 DArT markers, using the classic mixed model mapping and genomic selection model BSSV (Bayesian Stochastic Search Variable). Eleven markers significantly associated with ear rot resistance were identified, and four markers were associated by both methods. All markers were identified near genes which have functions that may be related to the resistance, requiring studies of their metabolic pathways.